ANALISIS PENERAPAN BLENDED LEARNING DI SEKOLAH DASAR - Nikku Panduning Hutami; Beni Azwar; Jumira Warlizasusi (Jurnal Isema : Islamic Educational Management, 2022)
The covid-19 virus poses new challenges for the whole world. All activities become disrupted including disrupting teaching and learning activities at school. During a pandemic like this, the world of education must change and modify learning that can be applied to this situation so that learning productivity can be achieved. Blended learning is a learning method that can be applied in the current situation. Blended learning is a learning method that combines face-to-face learning or classical learning with modern technology-based learning that is done online. Muhammadiyah Elementary School in Ketanggungan is one of the schools that applies this method. As long as this method is applied, it is considered effective for use during this pandemic, although it cannot be denied that there are also negative sides. By analyzing the application of blended learning, it is intended to be material for consideration of the school's leadership in choosing the right method for the application of the learning system during this pandemic, as well as being an evaluation material for Muhammadiyah Elementary School in Ketanggungan. The research method used in this research is descriptive qualitative, and the data collection method uses interviews and online observations.